Implementação de um currículo dos futebóis para a Educação Física nos anos finais do ensino fundamental - Barreto, Mariama Silva Gouvêa (Universidade Federal de São Carlos, 2023)
The proposal of this current study arises from the concerns about teaching soccer in school physical education, and above all the possibility to unlink this process from a technical perspective guided only in knowing how to do so. Regarding this problem, we elaborate a curriculum to teach soccer in the final years of elementary school. Soccer, itself is understood as a plural fenomenon , which has a room for diversity, overcoming the idea that the spectacularized soccer is the only one possible. The study aimed to investigate the elaboration of a soccer’s curriculum for physical education in the final years of elementary school, and the implementation of a didactic unit of this curriculum with a group of 8th graders of elementary school , and analyze the education processes emerging from this intervention. It is about qualitative research like a research-action marked by the implementation of a didactic unit, composed of 12 classes, guided with the internal and external logic of soccer. The data product instrument used was the class diary, having as sources the participant observations and the audio records. The collected data from the research were analyzed through the analysis of the codification categories in three steps: the organization and reading of the documents, codification and categorization of the materials. The results and their analysis are organized into a descriptive category referring to the description of curriculum development and its presentation, and three other analytical categories. The first is, “The students experience through soccer'', evidenced by the main experiences which emerged through the attending in the soccer classes, as well the genre relations that overtaken these experiences. The second is, “Soccer’s Curriculums'' denote the students' experience with soccer through the internal and external logic of the game, analyzing the consciousness tactic-technical and the dialogues and critical reflections about the political influence in soccer and, the third “Challenges and difficulties of the research teacher in the implementation of the Soccer’s curriculum” is focused on the self-analysis of the teaching experience with its limits and possibilities. It is considered that the soccer’s curriculum enables the students to have positive and inclusive experiences, and a learning guided by body, conceptual and attitudinal knowledge, giving them access to the soccer sociocultural dimension through the external logic of the game.
Implementation of a soccer’s curriculum in Physical Education for elementary school in the final years
Keywords: Educação física escolar; Ensino fundamental anos finais; Futebol; Futebóis; Currículo; School physical education; Elementary school final years; Soccer; Soccers; Curriculum; CIENCIAS DA SAUDE::EDUCACAO FISICA